2020
DOI: 10.12913/22998624/127437
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Comparison of the Hardness and Scratch-Resistance of the PMMA Polymers Used in Orthodontic Appliances

Abstract: The paper presents the studies and results of the Shore hardness and scratch test of polymer materials used in medical devices. Polymers of organic PMMA (poly(methyl methacrylate)) origin for the manufacture of orthodontic appliances were tested. Samples of test materials differed in manufacturing technology. The surface functional properties of four materials were compared. Hardness tests were performed with the Shore D hardness test method. The scratch test was done with a Rockwell diamond cone indenter. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Such forces can arise in orthodontic treatment of involuntary tooth clenching. The action of these forces can lead to permanent damage through local deformation of a material used for orthodontic appliances where concentrated biomechanical forces act, e.g., due to contact with canine cusps [ 70 ]. Orthodontic appliances that serve to prevent the effects of these diseases should take over these pathological forces and movements to relieve pressure on teeth without a loss of functionality when used by a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Such forces can arise in orthodontic treatment of involuntary tooth clenching. The action of these forces can lead to permanent damage through local deformation of a material used for orthodontic appliances where concentrated biomechanical forces act, e.g., due to contact with canine cusps [ 70 ]. Orthodontic appliances that serve to prevent the effects of these diseases should take over these pathological forces and movements to relieve pressure on teeth without a loss of functionality when used by a patient.…”
Section: Discussionmentioning
confidence: 99%
“…In [77] it was found that in the environment of physiological fluids a decrease in polymer creep resistance may occur, which may be associated with the diffusion of liquid particles between polymer chains. On the one hand, these particles can act as a plasticising agent and, on the other hand, as a factor causing stress corrosion, which accelerates the process of material destruction [78,79]. The coexistence of biomechanical forces and oral environment factors for several hours a day determines the durability of the biomechanical orthodontic appliance.…”
Section: Discussionmentioning
confidence: 99%
“…The Shore D hardness of the samples was measured by indentation with a durometer for hard rubbers, semi-rigid plastics and hard plastics according to [32]. Hardness was recorded after 3 s from the penetration of the indenter inside the tested epoxy sample.…”
Section: Hardnessmentioning
confidence: 99%